High‐throughput microsatellite marker development for the distylous herb Primula mistassinica (Primulaceae)1. (15th July 2013) - Matheny, Hannah; Edwards, Joan; Maroja, Luana S.
Abstract : Premise of the study: Twelve microsatellite markers were developed for Primula mistassinica, a distylous, diploid arctic‐alpine plant. The markers will be used to investigate the landscape genetics of a disjunct population on Isle Royale, Michigan, and the phylogeographic patterns of the species. Methods and Results: We used Roche/454 high‐throughput technology to sequence microsatellite‐enriched regions in the P. mistassinica genome. We developed 12 polymorphic microsatellite primer sets. These loci contained di‐, tri‐, and tetranucleotide repeats with two to nine alleles per locus when assessed in 23 individuals. Conclusions: Understanding the historical movements of P. mistassinica will provide insight to the survival prospects of current Arctic plant populations, which face the pressures of global, anthropogenic climate change.